Nasal polyps in childhood: insights from a pediatric pulmonology cohort - Kekeç, Handan; Şişmanlar Eyüboğlu, Tuğba; Çetinkaya, Ali Buğra; Kula, Nilgün; Bozdağ, Fatma; Aslan, Ayşe Tana (The Turkish Journal of Pediatrics, 2026)
Introduction. Nasal polyps (NP) are benign inflammatory growths originating from the nasal/paranasal sinus mucosa. NPs can occur independently or signify underlying respiratory conditions. This study aimed to evaluate the demographic and clinical characteristics of NPs in children at a pediatric pulmonology department. Method. This cross-sectional study included children aged 0-18 years diagnosed with NP at the pediatric pulmonology department from 2007 to 2025. Patients were categorized into four groups: cystic fibrosis (CF), primary ciliary dyskinesia (PCD), asthma/allergic rhinitis (AR), and undefined etiology. Demographic and clinical data were compared across these groups. Results. A total of 47 (40.4% female) patients were included in the study. The median age of NP diagnosis was 11 years (4.6-17.8). The most common presenting symptoms were nasal obstruction (47, 100%) and mouth breathing during sleep (37, 78.7%). The etiological causes of NPs were PCD (13, 27.7%), CF (9, 19.1%), asthma/AR (11, 23.4%), and an undefined etiology (14, 29.8%). Bilateral NPs were present in 32 (68.1%) cases. In 27 (57.4%) patients, NP was the first presentation, with no other symptoms. Among all PCD patients, NP was the first presentation in 7 (53.8%) of cases. NP recurrence was documented in 14 patients (29.8%). No significant differences were observed among the groups in sex, growth z-scores, or age at NP diagnosis (p>0.05). Bilateral NPs were more common in the PCD group (92.3%) than in the CF (66.7%), asthma/AR (36.3%), and undefined groups (71.4%) (p=0.034). NP recurrence was more frequent in the CF group (66.7%) compared with the PCD (38.5%) and undefined groups (13.6%), while no recurrence was observed in the asthma/AR group (p=0.021). Conclusion. This study highlights the heterogeneity of pediatric NP in causes, presentation, and course. Patients with PCD often present bilaterally, while CF patients have the highest recurrence rate. In PCD, NP was the initial sign in over half of cases, suggesting isolated NP should prompt suspicion of PCD.